Advanced Nursing Practice as a panacea for healthcare in Poland - Kazakidis, Katarzyna; Kryczka, Tomasz (Nursing in the 21st Century, 2021)
ADVANCED NURSING PRACTICE AS A PANACEA FOR HEALTHCARE IN POLANDIntroduction. Advanced Nursing Practice (ANP) is a relatively new concept in Poland. In order to be introduced, it needs a legal basis. There are specific regulations in Europe, yet they are only a framework for more detailed legislation in every member state of the European Union.Aim. To discuss Advanced Nursing Practice principles and the benefits for the national healthcare system resulting from implementing ANP in Poland.Discussion. Advanced Nursing Practice was defined in the 1950s in the United States of America. Presently in Europe and in Poland a definition by the International Council of Nurses (ICN) is applied. ICN has also defined the scope of competences for nurses of Advanced Practice. In Poland there already exist some regulations which substantially cover this scope. ANP implementation can naturally start in hospital settings. In ambulatory field ANP gives hope for effective transformation, namely increasing the efficiency and effectiveness of Primary Healthcare (pol. POZ) centers (comparable to General Practice in other countries).Conclusions. Effective implementation of ANP in Poland requires a slight modification of existing legal acts, a properly developed educational system and proven solutions or concepts derived from other European countries' experience.